Blacktip reef sharks, C archarhinus melanopterus , have high genetic structure and varying demographic histories in their I ndo‐ P acific range - Thomas M. Vignaud; Johann Mourier; Jeffrey A. Maynard; Raphael Leblois; Julia L.Y. Spaet; Eric Clua; Valentina Neglia; Serge Planes (Molecular Ecology, 2014)
For free‐swimming marine species like sharks, only population genetics and demographic history analyses can be used to assess population health/status as baseline population numbers are usually unknown. We investigated the population genetics of blacktip reef sharks, C archarhinus melanopterus ; one of the most abundant reef‐associated sharks and the apex predator of many shallow water reefs of the I ndian and P acific O ceans. Our sampling includes 4 widely separated locations in the I ndo‐ P acific and 11 islands in F rench P olynesia with different levels of coastal development. Four‐teen microsatellite loci were analysed for samples from all locations and two mitochondrial DNA fragments, the control region and cytochrome b , were examined for 10 locations. For microsatellites, genetic diversity is higher for the locations in the large open systems of the R ed S ea and A ustralia than for the fragmented habitat of the smaller islands of F rench P olynesia. Strong significant structure was found for distant locations with F ST values as high as ~0.3, and a smaller but still significant structure is found within F rench P olynesia. Both mitochondrial genes show only a few mutations across the sequences with a dominant shared haplotype in F rench P olynesia and N ew C aledonia suggesting a common lineage different to that of E ast A ustralia. Demographic history analyses indicate population expansions in the R ed S ea and A ustralia that may coincide with sea level changes after climatic events. Expansions and flat signals are indicated for French Polynesia as well as a significant recent bottleneck for M oorea, the most human‐impacted lagoon of the locations in F rench P olynesia.